Penerapan Aplikasi Siske Sakti Dalam Memanajemen Keuangan Santri Pondok Pesantren Al Mubarok Baturaja - Lisa Mulyani; Muhamad Yazid; Rendy Rianda Putra (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This study focuses on financial management in the field of education/agency at the Al Mubarok Baturaja Islamic Boarding School. Historically, financial management at the Al Mubarok Islamic boarding school was managed manually. Over time, financial management using the manual method is considered less efficient. Therefore, an application called Siske Sakti was created, which is a digital-based Islamic boarding school financial recording application, which has complete and simple features and design. This study uses the Field Research Method. While the Siske Sakti testing technique used beta testing which was carried out by distributing questionnaires via Google form to respondents, namely Al Mubarok students as many as 20 people using a Likert Scale. From the research that has been done, it is obtained that an average percentage of 80.36% is included in the